Identifikasi permasalahan implementasi pembelajaran pada masa pandemi di sekolah dasar - Galuh Ratna Palupi; Siti Wahyuningsih; Suharno Suharno (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
The research aims to identify implementation issues of learning at the time of the pandemic at SDN 3 Karangsambung in 2020 based on Environment-Load Theory. The method used in this research was a descriptive qualitative method. The subjects of this research were 1st-6th grade teachers at SDN 3 Karangsambung. Data were collected using in-depth interview techniques, observation, and document analysis. Data analysis techniques used were data reduction, data presentation, and deduction drawing. Analysis shows that problems have been found in the learning implementation process at the time of the pandemic at SDN 3 Karangsambung, namely lack of access to online learning activities, low levels of teacher and learner interaction, and lack of learning methods variations. According to the Environment-Load Theory, this problem stems from the amount of stimulus that must be accepted by the research subject of the environment. In accordance with the Environment-Load Theory, where stimulus received exceeds capacity, would create issues. Based on this study, it can be concluded that education implementation problems at the time of pandemic at SDN 3 Karangsambung due to the stimulus received by SDN 3 Karangsambung’s teachers. The study implicates to show identification of the implementation problems of learning based on the Environment-Load Theory that can be used to reference such studies and reference to schools, teachers, or others in policymaking regarding the implementation of learning.